Analisis Performa Transformator 2500 kVA Setelah Perbaikan Dan Purifikasi - Wasripin; Aripin Triyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The problem with transformers, especially those used in the supply of electrical power supply to high-rise buildings, is in the output voltage of the distribution transformer. Lifetime and continuous use cause a decrease in performance and transformer performance in supplying usage loads. There needs to be a solution to the transformer performance problem in order to save transformer efficiency costs on the use of electrical power against the load used. The research method used is to purify the transformer so that the transformer performance remains stable in supplying the load. The step in purification is to take measurements before and after at the transformer terminals to LVMDP. The result obtained is a voltage drop of 39% but still within the range of >30 kV, with an average load of 1145A. The average 3phase voltage after data purification is 405 Volts, after a purification period of 2 operational years it drops to 402 Volts. As for the 1phase voltage, data is obtained after purification of 235 Volts down to 231 Volts. The temperatur of the HV 400C transformer has increased to 44,80C.